Trend of liver cancer attributable to alcohol use in China from 1992 to 2021: An age-period-cohort analysis study - Zheng Tang; Ying Deng; Yuheng He; Yiyi Chen; Lu Qin; Jun Tian; Yuting Lei; Yongzhao Zhou; Zhi Wan; Dan Jia (PLoS ONE, 2026)
Background & aims To analyze the dynamic trends of mortality, incidence, and disability-adjusted life years (DALYs) of liver cancer attributable to alcohol use in China from 1992 to 2021, as well as the age, period, and cohort effects, so as to provide a basis for the prevention and control. Methods The data were sourced from the Global Burden of Disease Study 2021. The joinpoint regression model was used to assess the trend changes in mortality, incidence, and DALYs. The Age-Period-Cohort model was employed to estimate the independent effects of age, period, and cohort. Results From 1992 to 2021, the standardized incidence rate of liver cancer attributable to alcohol use in China increased annually by an average of 0.8% (95% CI: 0.5–1.1%), while the mortality rate rose by an average of 0.7% per year (95% CI: 0.3–1.0%), and the DALYs increased by an average of 0.6% annually (95% CI: 0.2–1.0%). The incidence and mortality rate ratio for men were approximately double those of women. The relative risk for individuals born between 1975 and 1985 increased 1.8-fold (95% CI: 1.5–2.1). Conclusion The disease burden has been on a continuous upward trend, with middle-aged men identified as high-risk groups. It is recommended to integrate liver cancer screening into the health management for high-risk populations.